2021
DOI: 10.3390/toxins13060381
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycin A in Cow’s Milk—A Pilot Study

Abstract: Hypoglycin A (HGA) originating from soapberry fruits (litchi, and ackee) seeds or seedlings from the sycamore maple (SM) tree (related to Sapindaceae) may cause Jamaican vomiting sickness in humans and atypical myopathy in horses and ruminants. A possible transfer into dairy cow’s milk cannot be ruled out since the literature has revealed HGA in the milk of mares and in the offal of captured deer following HGA intoxication. From a study, carried out for another purpose, bulk raw milk samples from four randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The LOD and LOQ for HGA, MCPrG, MCPA-glycine, MCPF-glycine, and MCPA-carnitine in milk and urine are summarized in Table 2 and Table 3 , respectively. The LOQ presented here for HGA in milk (1.12 µg/L) is noticeably lower than the limit of detection reported by Bochnia et al (9 µg/L) [ 29 ]. In urine, the LOQ for MCPA-glycine and MCPF-glycine of the proposed method were 78.9 and 41.6 µg/L, respectively, which are lower than the lowest limit reported in human urine by Isenberg et al (100 µg/L) [ 36 ].…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…The LOD and LOQ for HGA, MCPrG, MCPA-glycine, MCPF-glycine, and MCPA-carnitine in milk and urine are summarized in Table 2 and Table 3 , respectively. The LOQ presented here for HGA in milk (1.12 µg/L) is noticeably lower than the limit of detection reported by Bochnia et al (9 µg/L) [ 29 ]. In urine, the LOQ for MCPA-glycine and MCPF-glycine of the proposed method were 78.9 and 41.6 µg/L, respectively, which are lower than the lowest limit reported in human urine by Isenberg et al (100 µg/L) [ 36 ].…”
Section: Resultscontrasting
confidence: 68%
“…Maple trees are especially abundant in central Europe and the USA, which may pose a risk of animal intoxication following ingestion of maple seeds and seedlings. Previous reports have indicated that these toxins could pass into the milk of mare [ 27 , 28 ] and cows [ 29 ], consequently predisposing humans to a health risk if contaminated milk is ingested.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rumen chyme is less liquid and the ventral groove less developed which both limit the rumen bypass [ 30 , 48 ]. It has to be noted that HGA has been detected in cow’s milk [ 49 ]. In those cows, some HGA must have gotten through the rumen, which leads to the hypothesis that, under a high toxic pressure, even these grazers might be at risk of HGA poisoning.…”
Section: Discussionmentioning
confidence: 99%